New method for the estimation of homogeneity of individual judgements in psychoacoustical experiments - ARANOWSKA, Elżbieta; MANTURZEWSKA, Maria; ROGOWSKI, Piotr (Archives of Acoustics, 2007)
This paper presents a new indicator for the estimation of homogeneity of individual judgements in psychoacoustical experiments. The indicator may be also used in studies from other fields in which the judgements are obtained in the form of numerical values. Two examples of the application of the new indicator have been discussed: one for the assessment of cohesion of listeners’ judgements in a psychoacoustical experiment conducted with the use of the method of absolute magnitude estimation and the other one for the assessment of homogeneity of marks given by jury members in a music competition. In the latter case, a new aggregate measurement tool was also proposed for ranking of competition participants.